2012
DOI: 10.2503/jjshs1.81.80
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationship between Degree of Self-compatibility and Floral Traits in Lilium longiflorum Thunb. (Liliaceae)

Abstract: Lilium longiflorum is endemic to the islands of the Ryukyu Archipelago in Japan and to the eastern seacoasts and satellite islands of the mainland of Taiwan. The species is an important ornamental plant, and is cultivated throughout the world. Lilium longiflorum has long been regarded as a self-incompatible species but the existence of selfing in some natural populations was suggested by isozyme analysis in a previous study. To confirm the occurrence of self-compatible individuals and to clarify the evolutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
1
5
0
1
Order By: Relevance
“…Triploid L. lancifolium × diploid L. lancifolium did not produce seeds in this study or in the study by Noda (1986). Lilium species often show gametophytic selfincompatibility (Ichimura and Yamamoto, 1992;Sakazono et al, 2012), and self-incompatibility is one possible reason for the sterility in this cross combination, which was supported by the results that fertile seeds were obtained by a cut-style pollination. …”
supporting
confidence: 77%
“…Triploid L. lancifolium × diploid L. lancifolium did not produce seeds in this study or in the study by Noda (1986). Lilium species often show gametophytic selfincompatibility (Ichimura and Yamamoto, 1992;Sakazono et al, 2012), and self-incompatibility is one possible reason for the sterility in this cross combination, which was supported by the results that fertile seeds were obtained by a cut-style pollination. …”
supporting
confidence: 77%
“…Blaney & Roberts ; Roberts & Moeller ; Gray ; Roh & Wilkins ; Dole & Wilkins ; Holcomb & Berghage ; Sakazono et al . ; Kim et al . ).…”
Section: Discussionunclassified
“…Populations vary in self‐compatibility in its native range of Taiwan (Sakazono et al . ), and it is completely self‐compatible and autonomously self‐pollinating in its introduced range in Japan (Inagaki ) and South Africa (Rambuda & Johnson ). A molecular‐marker study in the native range showed that fixation indices ( F is ) of populations range from 0·032 to 0·901, suggesting variation among populations in mating system (Hiramatsu et al .…”
Section: Methodsmentioning
confidence: 99%